Hubungan Pengetahuan Dengan Kepatuhan Perawat Dalam Pelaksanaan Standar Prosedur Operasional (SPO) Pencegahan Risiko Jatuh Diruang Rawat Inap RSUD Ngimbang - Gofur, Abdul; Suratmi, Suratmi; Atmaji, M. Bakri Priyo Dwi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Patient safety is a top priority in healthcare services, and the prevention of fall risk is one of the key indicators in maintaining the quality of hospital care. At RSUD Ngimbang, the implementation of the Standard Operating Procedure (SOP) for fall risk prevention has not been optimal, which may increase the potential for patient fall incidents. One of the factors influencing nurses' compliance with the SOP is their level of knowledge. This study aims to determine the relationship between knowledge and nurse’ compliance with the implementation of the fall risk prevention SOP in the inpatient ward of RSUD Ngimbang. This research used a cross-sectional design and involved 73 nurses selected through cluster random sampling. The research instrument was a questionnaire, and data were analyzed using Spearman’s rho test. The results showed that the majority of nurses had good knowledge (59 nurses or 80.2%), and most were compliant in implementing the fall risk prevention SOP (56 nurses or 76.7%). Statistical analysis revealed a significance value of p = 0.000 (p < 0.05) and a correlation coefficient (r) = 0.451, indicating a significant relationship between knowledge and nurses' compliance with the SOP in the inpatient ward of RSUD Ngimbang. In conclusion, there is a significant positive correlation between knowledge and nurses’ compliance in implementing the fall risk prevention SOP. Therefore, improving nurses’ knowledge should be a priority in efforts to enhance patient safety.